Performing universal tasks on the Web: Interaction with digital content by people with intellectual disabilities - Rocha, Tânia (2015)
With this study we intent to better understand how a group with intellectual disabilities interacts with digital content, namely web content, when performing equivalent tasks from their daily school activities, such as: painting, making puzzles, playing games. To accomplish this we observed how a group with intellectual disabilities, without experience using computers, performed universal tasks (selection, manipulation and navigation) when presented with different activities on the Web such as painting, playing games or searching. We aimed at evaluating usability and accessibility and for this we registered the following variables: successful conclusion of activities, type of difficulties found, errors, satisfaction, motivation and autonomy indicators. Participants showed motivation and learning skills when performing all the three universal tasks (selection, manipulation and navigation) which is confirmed by the number of participants that was able to conclude the activities. Concerning errors, it was observed that despite the large number of errors made by the participants, their motivation lead them to complete the tasks. When handling the input devices the participants had a good performance using the computer mouse. On the other hand, they could not use the keyboard alone because of their reading/ writing difficulties.